Uji Aktivitas Antidiabetes Fraksi N-Heksan dan Etil Asetat dari Daun Areuy Kikunti Secara Invitro - Purwati Purwati; Rizki Afriandi (Syntax Corporation Indonesia, 2022)
Diabetes mellitus is a disease with metabolic disorders that are often found in Indonesian society. One of the natural components that can be used as antidiabetic are several plants from the genus pothos. In this study, using the results of the fraction of one of the plants of the genus Pothos, namely Pothos junghuhnii de Vraise and testing the inhibitory activity of the -glucosidase enzyme with Acarbose as a comparison. Antidiabetic activity test using microplate and analyzed with Elisa reader. The inhibitory activity value (% inhibition) was obtained at a concentration of 1000ppm for the n-hexane fraction, which was 7.2%, while for the ethyl acetate fraction, it was 48.6%. From the results shown, it has not been able to inhibit 50% of enzyme activity so that it is included in the weak category when compared to the inhibitory activity value (% inhibition) of acarbose which is 97%.